Rola i funkcje usług żywieniowych we współczesnym świecie - Zabrocki, Romuald (Space – Society – Economy, 2008)
According to the author, the increase and importance of catering services need to verify their principal functions necessary in modern world. The functionality of services in an important factor influencing the satisfaction of consumers in process of supplying their needs. Besides, it influences the overall quality of firms offering catering services. More important functions, not including principal ones, cover: industrial (profitable market section), social (integration, catering at workplace and hospitals), cultural (exposition and promotion of cultural values), educational (formation of cultural patterns), and pro-healthy functions (creation of proper food attitudes), marketing (promotion of new foods and meals), and distribution (sale of goods and additional services). The significance and importance of particular functions depends on a variety of factors as: nature of services, sort of catering firm, sort of consumers, etc. It seems that a majority of mentioned functions is so far underestimated resulting in wrong image of Polish gastronomy.